Square to the target? Coaching cues and technical analysis of the Australian football handball - Parrington, L.; Ball, K.; MacMahon, C. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Handball is an important skill in Australian Football. This study evaluated technical factors associated with handball accuracy by comparing successful and unsuccessful passes as well as evaluating current coaching cues used for the handball pass. Four elite Australian football players performed eight handballs with their preferred hand toward a bulls-eye target. Three dimensional kinematic data was collected and analysed between maximum backswing and ball contact to compare hits and misses. No significant differences were found for group results; however, medium effect sizes were found for hand velocity, hand path direction, elbow and humerus range of motion, humerus angle at ball contact and humerus angular velocity. Pelvis orientation toward the target showed a small effect. Data suggests further work in the area of handballing accuracy is warranted.